Quantifying variation in DLP‐ to‐ effective‐dose conversion factors in CT using a Monte Carlo‐based dose‐estimation software - Jelena M. Mihailovic; Renxin Chu; Da Zhang; Andrew M. Hernandez; Kai Yang; Lifeng Yu (Journal of Applied Clinical Medical Physics, 2026)
Abstract Background A common method to estimate the effective dose in CT is to multiply the dose length product in a CT scan by a conversion factor (k). The k‐factors are determined by dividing the effective dose (calculated using a weighted summation of organ doses) by the dose length product (DLP) for specific digital phantoms. The k‐factors determined in this way may vary substantially depending on the effective dose calculation methods and phantom models used. Purpose The purpose of this study was to estimate variation associated with different acquisition and patient characteristics in the quantification of k‐factors. Methods K‐factors were calculated using VirtualDoseCT for a diverse set of computational phantoms representing different patient models, scanner models, and seven CT exams. The tube potential varied from 80 to 120 kV. The scan length was varied by ± 5 cm relative to the default setting. The CTDIvol was set to 10 mGy when tube current modulation was not used; otherwise, the software default was used. A multivariable regression method was employed to derive an empirical formula for k‐factors, along with model‐uncertainty analysis and Sobol's sensitivity analysis to identify the influence of each variable. Results K‐factors for all exams increased with kV. Negative dependence of k‐factors on BMI was observed, with lower values in males than in females. Moderate to high variation was observed in the quantification of k‐factors without TCM, which remained unchanged with TCM. Based on Sobol's indices (0.8–1), k‐factors were influenced most by scan length and patient size for adults, and scan length and age for pediatric phantoms. Discussion The study showed that a large spread in k‐factors was predominantly influenced by scan length, patient size and age. The heterogeneity in k‐factors may lead to large heterogeneity in the effective dose estimate if the DLP×k method is used. These results indicate that age and size specific k‐factors to estimate effective dose from DLP may be warranted. Conclusions A set of k‐factors should be established to account for these factors and improve effective dose estimations.